2016
DOI: 10.21037/jtd.2016.07.07
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cardiopulmonary exercise testing parameters with quality of life in stable COPD patients

Abstract: Background: The precise head to head relationships between Cardio-pulmonary exercise testing (CPET) parameters and patients' daily symptoms/activities and the disease social/emotional impact are less well defined. In this study, the correlation of COPD daily symptoms and quality of life [assessed by St. George's Respiratory Questionnaire (SGRQ)] and COPD severity index (BODE-index) with CPET parameters were investigated. Methods: Symptom-limited CPET was performed in 37 consecutive COPD (GOLD I-III) subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
2
7
0
2
Order By: Relevance
“…, value ≤ 30%) is commonly used in the literature [4, 30, 31], but it remains wide, and it may not be adapted for all individuals. Indeed, recently Mirdamadi et al [32] have reported a mean ventilatory reserve = 30.9% (which is according to our study), but their study revealed also wide standard deviation (±25.1%). More specifically, their results showed a ventilatory reserve = 43.1 ± 25.6% in patients with leg fatigue and only a ventilatory reserve = 16.6 ± 15.4 in patients without leg fatigue [32].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…, value ≤ 30%) is commonly used in the literature [4, 30, 31], but it remains wide, and it may not be adapted for all individuals. Indeed, recently Mirdamadi et al [32] have reported a mean ventilatory reserve = 30.9% (which is according to our study), but their study revealed also wide standard deviation (±25.1%). More specifically, their results showed a ventilatory reserve = 43.1 ± 25.6% in patients with leg fatigue and only a ventilatory reserve = 16.6 ± 15.4 in patients without leg fatigue [32].…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, recently Mirdamadi et al [32] have reported a mean ventilatory reserve = 30.9% (which is according to our study), but their study revealed also wide standard deviation (±25.1%). More specifically, their results showed a ventilatory reserve = 43.1 ± 25.6% in patients with leg fatigue and only a ventilatory reserve = 16.6 ± 15.4 in patients without leg fatigue [32]. Consequently, it is possible that in the current study we have considered that CPET was maximal from ventilatory reserve ≤ 30% in COPD patients without leg fatigue, while a low ventilatory reserve should have been researched (approximately ≤ 15% in these patients).…”
Section: Discussionsupporting
confidence: 74%
“…Our findings were similar to those of Morishita-Katsu et al ( 36 ) who evaluated 109 subjects with stable COPD and observed a weak correlation between the SGRQ score and clinical and functional variables at rest. Regarding exercise, Mirdamadi et al ( 38 ) evaluated 37 patients with COPD (GOLD I-III) and found no significant correlation between peak VO 2 and the SGRQ score. Similarly, other researchers reported that peak VO 2 is a poor indicator of health status ( 3 , 39 ), suggesting that CPET parameters at peak exercise may not be effective for evaluating the ADLs of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Любые структурные заболевания сердечнососудистой системы (ССС), такие как АГ, ХСН, ишемическая болезнь сердца (ИБС) могут способствовать медленной, но неуклонно прогрессирующей структурной перестройке желудочков и предсердий, этот процесс происходит в связи с пролиферацией и заменой фибробластов на миофибробласты, а также усиленным отложением соединительной ткани и фиброзом [7]. По мере накопления знаний о патогенезе ФП, и, в первую очередь, о вкладе сопутствующих заболеваний в течение этого процесса, становится сомнительным существование первичной или идиопатической ФП [8]. В сравнительно недавнем масштабном исследовании European Heart Survey, участниками которого стали 3978 пациентов с ФП, частота идиопатического или первичного типа данной патологии наблюдалась всего лишь у 3% из выше указанного числа лиц, принимавших участие [9].…”
unclassified